Análisis del desarrollo social a través de la programación televisiva: imaginarios sociales juveniles en torno a los reality shows (combate, bln, calle 7) - Garzón Moreno, Jacqueline Ximena (2017)
The present research focuses on understanding the construction of Imaginaries by the youth of San Felipe neighborhood, in terms of entertainment content (Reality shows) created and disseminated by some media of the country (RTS, Canal UNO, TC Mi Canal ), in order to know the consumption habits of young audiences and how they perceive the content transmitted by these means. It is necessary to start from a brief account of the background and scientific basis of the subject matter raised. Starting from this description, on the consumption of Reality shows, the research will be carried out through the design of alternatives which allow the improvement of the social development of young people, knowing, identifying, studying and explaining the expected impacts during the whole investigation….